2014
DOI: 10.1016/j.regpep.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 released to the mesenteric lymph duct in mice: Effects of glucose and fat

Abstract: Using a newly developed in vivo model measuring glucagon-like peptide-1 (GLP-1) in gut lymphatics in mice, we quantified GLP-1 secretion in vivo after glucose versus fat ingestion with and without concomitant DPP-4 inhibition. The mesenteric lymphatic duct was cannulated in anesthetized C57BL6/J mice and lymph was collected in 30 min intervals. Glucose or fat emulsion (IntralipidR) (0.03, 0.1 or 0.3 kcal) with or without DPP-4-inhibition (NVP DPP728; 10 μmol/kg) was administered by gastric gavage. Basal intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…It has been reported that intestinal lymph flow may be reduced by anesthesia; but to mitigate this we used an anesthetic (␣-chloralose), which is mainly a hypnotic with minimal effect on gastrointestinal motility and secretion and enteric reflexes in pigs [9]. While our findings with respect to GLP-1 levels in lymph clearly contrast to the cited studies [1,3,17], D'Alessio et al reported, similar to our findings, lower DPP-4 activity in lymph when compared activity levels in plasma [3]. Thus, despite stimulating the secretion of GLP-1 to a similar extent as in the rodent studies (as evidenced from the prompt and robust increases in plasma concentrations), we were unable to demonstrate a corresponding increase in lymph levels, which remained low and relatively unchanged throughout the study.…”
Section: Fig 1 Total Glp-1 (A) and Intact Glp-1 (B) Levels (Pmol/l)contrasting
confidence: 75%
See 2 more Smart Citations
“…It has been reported that intestinal lymph flow may be reduced by anesthesia; but to mitigate this we used an anesthetic (␣-chloralose), which is mainly a hypnotic with minimal effect on gastrointestinal motility and secretion and enteric reflexes in pigs [9]. While our findings with respect to GLP-1 levels in lymph clearly contrast to the cited studies [1,3,17], D'Alessio et al reported, similar to our findings, lower DPP-4 activity in lymph when compared activity levels in plasma [3]. Thus, despite stimulating the secretion of GLP-1 to a similar extent as in the rodent studies (as evidenced from the prompt and robust increases in plasma concentrations), we were unable to demonstrate a corresponding increase in lymph levels, which remained low and relatively unchanged throughout the study.…”
Section: Fig 1 Total Glp-1 (A) and Intact Glp-1 (B) Levels (Pmol/l)contrasting
confidence: 75%
“…This could explain that much lower concentrations are found in the central core [7]. Tso et al previously found food stimulated GLP-1 levels in lymph from rats to be 10-fold higher than plasma (v.portae) levels increasing from about 15 (basal levels) to 300 pmol/l (total GLP-1), and Ohlsson et al recently reported increases in intact GLP-1 during glucose or fat stimulation from 0.5 to around 40 pmol/l in lymph from anaesthetized mice [1,3,17]. In the present study, NC resulted in robust increases in arterial GLP-1 concentrations (reaching 50 pmol/l), indicating that we achieved a similar degree of stimulation of secretion as in the rodent studies.…”
Section: Fig 1 Total Glp-1 (A) and Intact Glp-1 (B) Levels (Pmol/l)mentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of oral glucose dosing to infusion via the portal vein revealed similar enhancement in hepatic glucose uptake relative to peripheral presentation, which excludes a contribution from a gut-secreted factor, such as Glp-1 (54). Yet, secretion of Glp-1 upon feeding contributes to reduced glucose production in liver by augmenting glucose-stimulated insulin secretion from pancreas (55). Our data of oral but not peripheral glucose dosing reducing Rdh mRNA are consistent with these observations and support the physiological significance of the observation.…”
Section: Discussionmentioning
confidence: 89%
“…Duodenal lipids have been reported to enhance BAT thermogenesis via a CCK-1R in the small intestine [23]. In response to dietary lipids, gut peptides such as CCK, peptide YY, glucose-dependent insulinotropic peptide and glucagon-like peptide-1 are released from small intestine [3, 44, 75, 76]. The involvement of these gut peptides in the activation of BAT thermogenesis via intestinal CCK-1R requires further experiments.…”
Section: Discussionmentioning
confidence: 99%